A Tracer Study of BEED and BSED Graduates of the Visayas State University, Philippines - Rosario P. Abela; Lijueraj J. Cuadra; Mary Jean M. Sapan (JPAIR Institutional Research Journal)
One of the goals of every university is to produce quality graduates. The study was conducted to trace the graduates of Bachelor of Secondary Education (BSED) and Bachelor of Elementary Education (BEED) from SY 2005-2012. Survey questionnaires were used in gathering the data. Collected data were interpreted through frequencies and percentages. Results showed that there was a high employment rate for BSED and BEED graduates. The reasons why graduates changed their jobs were due to salaries and benefits. There were still unemployed and never-been-employed graduates because of no job opportunities. This implies that there were insufficient job vacancies/positions in the education sector. There should be an increase in salaries and benefits for regular/permanent workers to motivate them to stay on their jobs. The graduates found that the skills and knowledge they obtain from the university were useful to their jobs. Nevertheless, they still suggested further improvements of VSU's curriculum by providing more related trainings/seminars and workshops, adapting K to 12 curriculums, and offering more communication/human-relation-skills courses. Future enrollees in BSED and BEED degrees should be given an oral interview first to determine if they have a strong passion for the profession.